Persistence of endocrine disruption in zebrafish (Danio rerio) after discontinued exposure to the androgen 17β-trenbolone - Baumann, Lisa; Knörr, Susanne; Keiter, Susanne; Nagel, Tina; Rehberger, Kristina; Volz, Sina; Oberrauch, Sophia; Schiller, Viktoria; Fenske, Martina; Holbech, Henrik; Segner, Helmut; Braunbeck, Thomas (Environmental toxicology and chemistry, 2014)
The aim of the present study was to investigate the effects of the androgenic endocrine disruptor 17β-trenbolone on the sexual development of zebrafish (Danio rerio) with special emphasis on the question of whether adverse outcomes of developmental exposure are reversible or persistent. An exposure scenario including a recovery phase was chosen to assess the potential reversibility of androgenic effects. Zebrafish were exposed to environmentally relevant concentrations of 17β-trenbolone (1 ng/L-30 ng/L) from fertilization until completion of gonad sexual differentiation (60 d posthatch). Thereafter, exposure was either followed by 40 d of recovery in clean water or continued until 100 d posthatch, the age when zebrafish start being able to reproduce. Fish exposed for 100 d to 10 ng/L or 30 ng/L 17β-trenbolone were masculinized at different biological effect levels, as evidenced from a concentration-dependent shift of the sex ratio toward males as well as a significantly increased maturity of testes. Gonad morphological masculinization occurred in parallel with decreased vitellogenin concentrations in both sexes. Changes of brain aromatase (cyp19b) mRNA expression showed no consistent trend with respect to either exposure duration or concentration. Gonad morphological masculinization as well as the decrease of vitellogenin persisted after depuration over 40 d in clean water. This lack of recovery suggests that androgenic effects on sexual development of zebrafish are irreversible. Environ Toxicol Chem 2014;33:2488-2496. © 2014 SETAC